Lecture 7 Notes

5 y 3y 10y x2 e5x yp x ax2 e5x yp x 2axe5x

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: d coefficients (3.5) y ￿￿ + 3y ￿ − 10y = x2 e−5x yp (x) = Ax2 e−5x ￿ yp (x) = 2Axe−5x − 5Ax2 e−5x ￿￿ yp (x) = 2Ae −5x −10yp (x) = ￿ 3yp (x) ￿￿ yp (x) = − 10Axe −5x − 10Axe −5x + 25Ax e 2 −5x − 10Ax e 2 −5x 6Axe −5x − 15Ax e 2 −5x = 2Ae−5x − 20Axe−5x + 25Ax2 e−5x Method of undetermined coefficients (3.5) y ￿￿ + 3y ￿ − 10y = x2 e−5x yp (x) = Ax2 e−5x ￿ yp (x) = 2Axe−5x − 5Ax2 e−5x ￿￿ yp (x) = 2Ae −5x − 10Axe −5x −10yp (x) = ￿ 3yp (x) ￿￿ yp (x) − 10Axe −5x + 25Ax e 2 −5x − 10Ax e 2 −5x = 6Axe −5x − 15Ax e 2 −5x = 2Ae−5x − 20Axe−5x + 25Ax2 e−5x 2Ae −5x − 14Axe −5x +0 Method of undetermined coefficients (3.5) y ￿￿ + 3y ￿ − 10y = x2 e−5x yp (x) = Ax2 e−5x ￿ yp (x) = 2Axe−5x − 5Ax2 e−5x ￿￿ yp (x) = 2Ae −5x − 10Axe −5x −10yp (x) = ￿ 3yp (x) ￿￿ yp (x) − 10Axe −5x + 25Ax e 2 −5x − 10Ax e 2 −5x = 6Axe −5x − 15Ax e 2 −5x = 2Ae−5x − 20Axe−5x + 25Ax2 e−5x 2Ae −5x − 14Axe −5x +0 =x e 2 −5x Method of undetermined coefficients (3.5) y ￿￿ + 3y ￿ − 10y = x2 e−5x yp (x) = Ax2 e−5x...
View Full Document

Ask a homework question - tutors are online